Penilaian Risiko Keselamatan Dan Kesehatan Kerja Dengan Menggunakan Metode Hirarc Dan Safety Policy - Eko Wahyu Abryandoko (Rekayasa Sipil, 2018)
Occupational Safety and Health is an important part of the company, especially in construction work, because the main factor for a company to achieve the desired goal is employee productivity, supported by a sense of security and comfort.. This study has developed this procedure based on observations with reference to the OHSAS 18001: 2007 standard certification of HIRARC method of applying SMK3 based on HIRARC preparation on job implementation. After the risk analysis is done based on HIRADC and Risk of Risk then there should be risk control. Efforts made to control by considering the hierarchy of elimination, substitution, technical control, administrative and equipment supply K3 namely by adjusting the completion time of the TJBTB Main Office Construction project